Análise dos efeitos do 2,6-Diisopropilfenol sobre a eletrofisiologia cardíaca em pacientes com ectopias de via de saída ventricula - Távora, Ronaldo Vasconcelos (2017)
Propofol is an effective hypnotic agent for the induction and maintenance of anesthesia. Recent studies have demonstrated that this drug exerts effects on the cardiac conduction system having both pro-arrhythmic and antiarrhythmic effects in a concentration-dependent manner. These effects seem to be more important when the mechanism involved in arrhythmias is hyperautomatism with few effects on reentrant arrhythmias. The mechanisms involved in such effects remain poorly defined, but possibly involve ion channels such as sodium, calcium, and potassium as well as modulations in the autonomic nervous system. However, we have not found in the literature studies on the effects of propofol on post-potency-triggered arrhythmias that represent one of the most frequent types of ventricular arrhythmias. The suspicion that the infusion of this agent can suppress this type of arrhythmia causes propofol to be deferred as sedative drug in electrophysiological study procedures that aim at the ablation of foci of this arrhythmic disorder. Such practice is based on individual observations and has no backing in scientific publications. The objective of this work is to propose a study model for the evaluation of the interference of 2,6-diisopropylphenol in cardiac electrophysiological variables and to analyze the effects of propofol on arrhythmias that conceptually have as a mechanism the activities triggered by late post-potentials. Ten patients with ventricular outflow tract arrhythmias without structural heart disease were selected and indicated for the treatment of ablation. All patients had an expressive number of ventricular extrasystoles (> 10% of total beats) detected on holter / 24h examination. Diagnostic catheters were positioned in the coronary sinus, right ventricle and anteroseptal region of the tricuspid ring for atrial, ventricular and HIS potentials, respectively. At baseline and under programmed atrial and ventricular pacing, data were collected from 17 (seventeen) cardiac electrophysiological variables: heart rate, QRS complex duration, atrial and ventricular command threshold, atrial conduction time, AH and HV intervals, Ventricular-atrial conduction, anterograde and retrograde Wenckebach points, effective retrograde anterograde and retrograde atrioventricular refractory periods, effective refractory periods of the right atrium and ventricle, coupling interval, and number of extrasystoles recorded within 5 minutes. These variables were collected before and during the intravenous infusion of propofol aiming to achieve a target sedation titrated by bispectral index (BIS) between 40 and 60. Analysis of the data presented showed that the infusion of propofol in doses titrated by the bispectral index did not seem to interfere in the Expression of ventricular arrhythmias triggered by late post-potentials when these were manifested as ventricular extrasystoles.